Achievements, challenges, and developing directions of bio-inspired self-repairing technology. (May 2021) - Duo, Li; Xiubin, Liu; Qingqi, Zhuo; Yanling, Qian; Yue, Li
Abstract: Bio-inspired self-repairing technology (BISRT), inspired by biological self-healing processes and multicellular structure, can dynamically adjust its structure to the faulty region on a flexible artificial multicellular substrate. The topic of bio-inspired self-repairing technology has been widely discussed since the 1990s, and over the past decades, this technology has been increasingly acknowledged in various domains. Though many initiatives were proposed, there are still bottlenecks hindering effective applications. In this paper, various methods and structures used in bio-inspired self-repairing technology are exhibited in a systematic way. Main challenges toward effective applications are elucidated and analyzed. The performance of different hardware structures is compared. Based on the studies of configuration information, a design flow of bio-inspired self-repairing technology is also presented. Moreover, the realizability of quantitative design at each phase is discussed and some future works are identified.